Predictability of Industry Momentum Portfolio Returns - Han-Hsing Yu, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The paper examines whether the returns of industry portfolios predict industry momentum portfolio returns. The results show a significant number of industry returns, including entertainment, medical equipment, and precious metals, forecast the industry momentum portfolios. To find industry momentum portfolios based on recent past are more predictable than those based on intermediate horizon past performance. Tests of economic significance show that the predictability of industry momentum returns is economically significant.